Biomarkers for grain yield stability in rice under drought stress - Melandri, Giovanni; AbdElgawad, Hamada; Riewe, David; Hageman, Jos A.; Asard, Han; Beemster, Gerrit T.S.; Kadam, Niteen; Jagadish, Krishna; Altmann, Thomas; Ruyter-Spira, Carolien; Bouwmeester, Harro (Oxford University Press, 2020)
The metabolic-oxidative stress profile of the rice flag leaf during drought stress in the reproductive stage is highly predictive for grain yield loss sensitivity of 292 accessions at harvest time.